Effect of user puffing topography on total particulate matter, nicotine and volatile carbonyl emissions from narghile waterpipes. (12th August 2019) - Eddingsaas, Nathan C; Hensel, Edward C; O'Dea, Sean; Kunselman, Peyton; DiFrancesco, A Gary; Robinson, Risa J
Abstract : Objectives: Puffing topographies of waterpipe users vary widely as does the puff-to-puff topography of an individual user. The aim of this study was to determine if puff duration and flow rate have an effect on the characteristics of the mainstream emission from waterpipes, including total particulate matter (TPM), mass ratio of nicotine and mass concentration of volatile carbonyls. Methods: Puffing parameters were chosen to encompass a significant portion of the perimeter space observed from a natural environment study. Tested conditions were 150, 200 and 250 mL sec -1 ; each run at 2, 3.5 and 5 s durations; 25 s interpuff duration and ~100 puffs per session. Each session was run in quadruplicate using the Programmable Emissions System-2 (PES-2) emissions capture system under identical conditions. Particulate matter, for quantification of TPM and nicotine, was collected on filter pads every ~5 L of aerosol resulting in 6 to 25 samples per session. Volatile carbonyls were sampled using 2, 4-Dinitrophenylhydrazine (DNPH)-coated silica. Results: Mass concentration of TPM linearly decreased with increased flow rate, with no dependency on puff duration. Nicotine mass ratio was independent of topography, with average mass ratio of nicotine to TPM of 0.0027±0.0002 (mg/mg). The main carbonyls observed were acetaldehyde and formaldehyde. Puff duration increased emissions of some carbonyls (eg, formaldehyde) but not others (eg, acetaldehyde). Conclusions: The results presented here highlight that topographies influence the emissions generated from waterpipes including TPM, total nicotine and volatile carbonyls. For laboratory studies to be representative of user exposure, a range of topographies must be studied. Using a range of topographies within a controlled laboratory environment will better inform regulatory policy.